Lossy and noisy channel simulation in computational ghost imaging by using noise-induced pattern - Jaesung Heo; Junghyun Kim; Taek Jeong; Sangkyung Lee; Yong Sup Ihn; Zaeill Kim; Yonggi Jo (Scientific Reports, 2022)
Abstract We provide a method to evaluate effects of a lossy and noisy optical channel in computational ghost imaging (CGI) technique. Instead of preparing an external noise source, we simulate the optical channel with a basic CGI experiment using programmatically generated noise-induced patterns. By using our method, we show that CGI can reject a noise of which intensity is similar with an imaging signal intensity at a target. The results with our method are well matched with experimental ones including external noise source. This method would provide useful knowledge to analyze environmental effects in CGI without realization of the environment.